Alternatives of Low Cost Soil Moisture Monitoring Devices for Vegetable Production in South Miami-Dade County - Rafael Muñoz-Carpena; Yuncong Li; Teresa Olczyk (EDIS)
This document is ABE 333, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: October 2002.